Emphasis Method in the Thirtieth Part of the Holy Quran - Erayer, Rafid Difar (International Journal of Psychosocial Rehabilitation, 2020)
This research dealt with the method of affirmation in the thirtieth part of the Holy Qur’an, as it dealt with the definition of the term assertion language and terminology, and the first topic dealt with (assertion types), while the second topic dealt with (moral affirmation and affirmation in extra letters and affirmation of letters and affirmation of the source and affirmation with some vocalizations) while the third topic dealt with (Emphasis by methods).